THE ROLE OF LAW IN INCREASING THE IMPLEMENTATION OF INFORMED CONSENT IN HOSPITALS BASED ON HEALTH LAW NUMBER 17 OF 2023 - Syifa Nadya Azzahra; Irsyam Risdawati; Marice Simarmata (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Informed consent is one of the fundamental aspects in medical practice, emphasizing the patient's right to give consent based on full understanding of the medical procedures they are about to undergo. The proper implementation of informed consent is crucial to safeguard the patient's rights and ensure that medical actions are performed ethically and professionally. The Health Law No. 17 of 2023 provides a clear legal foundation regarding the obligations of hospitals and medical personnel in carrying out informed consent. Article 56 of this Law states that "every medical professional conducting medical procedures must provide sufficient information to the patient to obtain written consent before performing the medical procedure." This regulation aims to protect the patient's rights and improve the quality of healthcare services in hospitals. This research aims to analyze the role of law in enhancing the quality of informed consent implementation in hospitals, referring to Health Law No. 17 of 2023. The research method used in this study is normative legal research with a descriptive-analytical approach. This approach is used to examine the regulations related to informed consent, as well as its implementation in medical practice in hospitals. The research findings indicate that although Health Law No. 17 of 2023 provides a strong legal foundation, the implementation of informed consent in hospitals still faces various challenges. The main obstacles identified include the lack of understanding by both patients and medical professionals regarding the correct procedures, as well as insufficient oversight in the implementation of this policy. This study recommends enhancing training for medical personnel and implementing stricter supervision of informed consent practices in hospitals. of your findings.